2022
DOI: 10.1093/ntr/ntac115
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Increase in the U.S. Smoking Cessation Rate and Its Implication for Future Smoking Prevalence

Abstract: Introduction We calculate the U.S. adult smoking cessation rate for 2014-2019, compare it to the historical trend, and estimate the implication for future smoking prevalence. Methods We repeated an earlier analysis, which examined the cessation rate from 1990-2014, extending the period to 2019. Employing National Health Interview Survey (NHIS) and National Survey on Drug Use and Health (NSDUH) data, we estimated the adult ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 12 publications
2
17
2
Order By: Relevance
“…Considering our CSMs (CSM-II to CSM-V), the vast majority did not. In addition, a recent study by Méndez et al revealed that the adult smoking cessation rate in the US has continued to increase, from 4.2% in 2008 to 2013 to 5.4% to 2014 to 2019. This large increase exceeded the rate expected on the basis of the trend over time .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering our CSMs (CSM-II to CSM-V), the vast majority did not. In addition, a recent study by Méndez et al revealed that the adult smoking cessation rate in the US has continued to increase, from 4.2% in 2008 to 2013 to 5.4% to 2014 to 2019. This large increase exceeded the rate expected on the basis of the trend over time .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study by Méndez et al revealed that the adult smoking cessation rate in the US has continued to increase, from 4.2% in 2008 to 2013 to 5.4% to 2014 to 2019. This large increase exceeded the rate expected on the basis of the trend over time . The cessation rate has become especially large for young adults, and the smoking initiation rate has decreased greatly during the same period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research is needed to examine the associations of age, cohort, and period with nicotine dependence. Sixth, success of cessation treatments, increases in cigarette prices through taxation, and implementation of smoking-free air laws help reduce cigarette consumption and increase cessation rates over time . Future research is needed to fully understand how these factors impact patterns in nicotine dependence among US adults with cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, success of cessation treatments, increases in cigarette prices through taxation, and implementation of smoking-free air laws help reduce cigarette consumption and increase cessation rates over time. 1,24,32…”
Section: Limitationsmentioning
confidence: 99%